Biomimetic RNA‐Silencing Nanocomplexes: Overcoming Multidrug Resistance in Cancer Cells1. (20th January 2014) - Wang, Zhongliang; Wang, Zhe; Liu, Dingbin; Yan, Xuefeng; Wang, Fu; Niu, Gang; Yang, Min; Chen, Xiaoyuan
Abstract RNA interference (RNAi) is an RNA‐dependent gene silencing approach controlled by an RNA‐induced silencing complex (RISC). Herein, we present a synthetic RISC‐mimic nanocomplex, which can actively cleave its target RNA in a sequence‐specific manner. With high enzymatic stability and efficient self‐delivery to target cells, the designed nanocomplex can selectively and potently induce gene silencing without cytokine activation. These nanocomplexes, which target multidrug resistance, are not only able to bypass the P‐glycoprotein (Pgp) transporter, due to their nano‐size effect, but also effectively suppress Pgp expression, thus resulting in successful restoration of drug sensitivity of OVCAR8/ADR cells to Pgp‐transportable cytotoxic agents. This nanocomplex approach has the potential for both functional genomics and cancer therapy.